3D digital light processing of redox-active polymers for electrochemical applications - Delavier, Christian; Bechtold, Svenja; Dodds, Marcus; Blasco, Eva; Ludwigs, Sabine (Advanced functional materials, 2025)
A novel approach for the 3D printing of electrochemically switchable conducting polymers by combining Digital Light Processing (DLP) with the redox-activity of carbazole-based polymer materials is presented. Complex 2D and 3D architectures are accessible by fast and versatile processing using a novel ink formulation. The printed polymer materials not only retain their redox-active response, but enable post-printing electrochemical manipulation throughout the printed structure, here demonstrated by elongation of the redox system via electrochemical crosslinking. Cyclic voltammetry coupled with in-situ spectroscopy provides insights into these redox processes and the optical changes during electrochemical doping of the 3D printed structures. Highlights include pixel-level electrochemical control via a chessboard design and color front visualization through a pyramid architecture. The integration of high-resolution 3D printing with redox-active materials opens new avenues in a wide range of applications in 3D printed (opto)electronics and switchable electrochemical devices.
Gesehen am 17.02.2026